PRICE DETERMINATION OF CHICKEN PORRIDGE MSMEs IN FACING RAW MATERIAL COST FLUCTUATION - Faizal Haris Eko Prabowo (Journal of Management Review, 2019)
The culinary industry is currently one of the best industries that are developing, this has become one of the economic supports in several regions. Based on the results of the economic census report of the Tasikmalaya City in 2016 the culinary industry in percentage and number of positions was in the third position followed by the large trade industry which occupied the first position and the processing industry in the second position. This study aims to determine the impact of changes in raw material costs lucratively on the selling price determination of chicken porridge in MSMEs at the City of Tasikmalaya. The population in this study were all MSMEs chicken porridge entrepreneurs totaling 261 units, while the method used in this study was a survey method with a quantitative approach presented descriptively. The result of this study is that changes in raw material costs have an impact of 89.2% on the determination of the selling price of chicken porridge. In fact, this is clearly illustrated by the chicken porridge activists who prefer to set the selling price using a mixed method based on market costs and demand. This is because there is a concern from chicken porridge activists for the risks that they will get such as decreasing sales and automatically reducing their revenue streams.